Barriers to mammography screening among racial and ethnic minority women. (October 2019) - Miller, Brittany C.; Bowers, Jennifer M.; Payne, Jackelyn B.; Moyer, Anne
Abstract: Rationale: Breast cancer is the second leading cause of cancer death among women. Disparities in breast cancer mortality rates adversely affect racial/ethnic minority women. Mammography screening is the most effective early detection method and means of reducing mortality rates. Yet, barriers prevent racial/ethnic minority women from participating in regular screening. Objective: This review aimed to summarize self-reported barriers to mammography screening in racial/ethnic minority women in studies using open-ended assessments and closed-ended assessments. Method: Literature searches were conducted in two databases, PsycINFO and PubMed. Barriers were detailed in full by barrier type (psychological/knowledge-related, logistical, cultural/immigration-related, and social/interpersonal) and summarized briefly by race/ethnicity (African American/Black, Asian/Pacific Islander, Hispanic, American Indian/Native American, and Middle Eastern). Results: Twenty-two open-ended and six closed-ended studies were identified as eligible for this review. Overall, racial/ethnic minority women identified common logistical and psychological/knowledge-related barriers. Additionally, women reported cultural/immigration-related and social/interpersonal barriers that were closely tied to their racial/ethnic identities. Conclusions: It was concluded that cultural/immigration-related barriers may be the only barrier type that is unique to racial/ethnic minority women. Thus, designing studies of barriers around race and ethnicity is not always appropriate, and other demographic factors are sometimes a more important focus. The variability in 'barrier' definitions, how data were collected and reported, and the appropriateness of closed-ended measures were also examined. This literature may benefit from detailed and strategically designed studies that allow more clear-cut conclusions and better comparison across studies as well as improving closed-ended measures by incorporating insights from investigations using open-ended inquiry. Highlights: Racial minority women commonly report logistical mammography barriers. Racial minority women report mammography barriers specific to their identities. Race-specific measures of mammography barriers exclude some relevant barriers.